Factors Associated with Early Marriage in Rural Mid-Western Nepal - Yogi, Belpatra Nath (Journal of Health Promotion, 2020)
Early (or child) marriage is a global public health issue influenced by a complex web of factors including socio-demographic conditions of the people. The present paper aims to examine factors associated with early marriageamong the people in rural communities of Nepal. A cross-sectional end-line study was carried out among 155 married respondents selected through cluster cum convenience sampling from six clusters of two rural districts of Mid-western Nepal. The mean age at first marriage was 18.4 years (SD=3.83). Two-third of them had an early marriage and the proportion of early marriage was remarkably higher among women than men (77.8% vs. 42.6%). The prevalence of early marriage was the most common among those of women, age-group of 35-44 years, illiterate and basic literate ones, nuclear and small families, and Janajatis. Sex and educational status of the respondents had a statistically significant association with their marital age (p < 0.05) and were major factors associated with early marriage but other socio-demographic factors such as age, caste/ethnicity, family type, family size and source of income were notfound directlyassociated with early marriage for the sample. Future research efforts should prioritize gender-transformative interventions to recognize and confront inequitable gender norms and actions.